Expression of D20-40 and CD in patients with colorectal carcinoma - Kashman, Basim M.; Hussein, Areej A.; Ibrahim, Basim M. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Colorectal is a worldwide health problem. Tumors stimulate the ground of host blood vessels, a process called angiogenesis, which is essential for supplying nutrients of the tumor, also stimulate the lymphatic vessels for metasatasis.